AN ANOMALY WITHIN AN ANOMALY: THE HALLOWEEN EFFECT IN THE LONG-TERM REVERSAL ANOMALY - King Fuei Lee (Tuwhera Open Access Publisher, 2021)
In this paper, we investigate the presence of the Halloween effect in the long-term reversal anomaly in the US. When we examine the cross-sectional returns of winner-minus-loser portfolios formed on prior returns over the time period of 1931-2021, we find evidence of stronger returns during winter months versus summer months. In particular, the effect appears to be driven by very strong winter-summer seasonality in the portfolio of small-capitalisation losers, and lack of Halloween effect in the portfolio of large-capitalisation winners. Our finding is robust to alternative measures of long-term reversal, differing sub-periods, the inclusion of the January effect and outlier considerations, as well as within small and large-sized companies.